PROBLEMS OF MASTERING LATVIAN AS A SECOND LANGUAGE IN THE CONTEXT OF THE DEVELOPMENT OF APPLIED LINGUISTICS - Lazdiņa, Sanita (Via Latgalica, 2008)
The objective of the paper is to illuminate the interpretation of the term „Applied Linguistics” in Latvia and abroad (in Western Europe, the USA and Russia), and thereby identifying possibilities and grounds for the research of Latvian as a second language in the context of the development of applied linguistics in Latvia. Apart from theoretical literature, the author also uses data from observations of classroom discussions, which were obtained in three secondary schools and one elementary school (two schools in Rezekne, one in Rezekne region and one in Balvi). The author of the paper conducted a discourse research of Grade 9 pupils who learn Latvian as a second language (LAT 2). These research data are also important for problems of the development of methodology of applied linguistics in Latvia, because they enable the identification of new data and research methods. Applied linguistics as a field is based on the research of language and its role in human activities. Modern research of applied linguistics in Western Europe shows that attention is paid to areas such as second language acquisition (SLA), cognition, language policy and planning, lexicography, translation theory, corpus linguistics, etc. In Russia, when defining the areas and functions of applied linguistics, emphasize is put on the close connection of linguistics with information technology, artificial intelligence and logics. Russian linguists link the emergence of applied linguistics to the development of science and technology, which have made it necessary to observe language in action. The term „Applied Linguistics” is usually opposed to theoretical linguistics, which studies language in a system under a particular condition. To identify the interpretation of the term „Applied Linguistics” in Latvia, two sources were used for the paper: The „Interpretative Dictionary of Basic Terms of Linguistics” (IDBTL), published in 2007, and the description of the branches and sub-branches of science available on the home page of the Latvian Council of Science (LCS). The comparison of these sources reveals two differences in the definition of „applied linguistics”. IDBTL does not mention sociolinguistics among the areas of applied linguistics. Sociolinguistics is mentioned separately in the dictionary, but there is no link to applied linguistics. The second difference is that IDBTL does not refer to language teaching or learning – neither in the definition of applied linguistics, nor in the description of its areas, whereas it is mentioned in the LCS description of sub-branches. These findings show a lack of consistency in introducing the problem of second language acquisition into the context of the development of applied linguistics. The second part of the paper gives an insight into the research of the Latvian language as a second language. The research data were obtained through structural observations of class discourse and by analyzing them with the help of check lists and tables. The data of the class discourse research is important for the research of the actual situation of language acquisition. The task of an applied linguist is to be a mediator between the theory of linguistics and language pedagogy (linguodidactics). Even for studying problems of mastering the Latvian language as a second language, there is still a lack of systemic research which would provide a deeper analysis of the difficulties that LAT2 pupils deal with while learning Latvian, as well as while studying other subjects bilingually or in Latvian. There is an on-going need for class discourse research and for research of a individual language acquisition processes by means of interviews, questionnaires, and pupils’ reports about the accomplishment of some cognitive or linguistic tasks, as well as by other methods.